Characterization and Regulation of the Osmolyte Betaine Synthesizing Enzymes GSMT and SDMT from Halophilic Methanogen Methanohalophilus portucalensis - Lai, Shu-Jung; Lai, Mei-Chin (PLOS ONE, 2011)
The halophilic methanoarchaeon Methanohalophilus portucalensis can synthesize the osmolyte betaine de novo in response to extracellular salt stress. Betaine is generated by the stepwise methylation of glycine to form sarcosine, N, N-dimethylglycine and betaine by using S-adenosyl-L-methionine (AdoMet) as the methyl donor. The complete gene cluster of Mpgsmt-sdmt was cloned from Southern hybridization and heterologous expressed in E. coli respectively. The recombinant MpGSMT and MpSDMT both retained their in vivo functional activities in E. coli BL21(DE3)RIL to synthesize and accumulate betaine and conferred elevated survival ability in betaine transport deficient mutant E. coli MKH13 under high salt stress. The dramatic activating effects of sodium and potassium ions on the in vitro methyltransferase activities of MpGSMT, but not MpSDMT or bacterial GSMT and SDMT, revealed that GSMT from halophilic methanoarchaeon possesses novel regulate mechanism in betaine biosynthesis pathway. The circular dichroism spectra showed the fluctuated peaks at 206 nm were detected in the MpGSMT under various concentrations of potassium or sodium ions. This fluctuated difference may cause by a change in the β-turn structure located at the conserved glycine- and sarcosine-binding residue Arg167 of MpGSMT. The analytical ultracentrifugation analysis indicated that the monomer MpGSMT switched to dimeric form increased from 7.6% to 70% with KCl concentration increased from 0 to 2.0 M. The level of potassium and sodium ions may modulate the substrate binding activity of MpGSMT through the conformational change. Additionally, MpGSMT showed a strong end product, betaine, inhibitory effect and was more sensitive to the inhibitor AdoHcy. The above results indicated that the first enzymatic step involved in synthesizing the osmolyte betaine in halophilic archaea, namely, GSMT, may also play a major role in coupling the salt-in and compatible solute (osmolyte) osmoadaptative strategies in halophilic methanogens for adapting to high salt environments.